States and countries in the unifying Europe - Tóth, József (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
The paper is dealing with the issue of the state borders in the unifying Europe, underlining the question of conflict borders and function of regions in the concept of the Europe of regions. On different case studies the suitability and its functionality are presented, of borders over the mainly inthe framework of regions.
Keywords: državne meje; Europe; Evropa; meje; obmejna območja; obmejno sodelovanje; regije